Manj znano in neznano o rodbini, zasebnosti in karierni poti mariborskega župana Andreasa Tappeinerja - Hozjan, Andrej (Studia Historica Slovenica, 2017)
Andreas Tappeiner (1810-1868) was without a doubt one of the most successful mayors in the 19th century. Born as a citizen of Maribor, he was also one of the most dynamic of citizens - locals of his time. He was mayor between 1861-1867, and before that he was also mayor in Lovrenc na Pohorju (1850-1853). He enhanced his mayoral career by holding the simultaneous position of representative of the city in the Provincial Assembly of Styria and for a short time also with the position as Head of District Representation in Maribor. Because of a long running mysterious disease he resigned from all posts just two months before he died. If his public life reads almost as a perfect story of career success, much less is known of his family (father, mother, brothers and sisters) and his private life. The centre of this piece is the exploration of lesser known images of the private life of the Tappeiner family in Celje and Maribor, with focus on Andreas and his father Johann. In this exploration the author attempts to remain impartial and realistic. Also published in this piece for the first time are photographs from his private archival unit held by the Maribor Regional Museum.
Keywords: 19.st.; Maribor; Tappeiner (rodbina); Tappeiner, Andreas; zgodovina; župani